2002
DOI: 10.3171/jns.2002.97.2.0250
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-early surgery for aneurysmal subarachnoid hemorrhage: outcomes for a consecutive series of 391 patients not selected by grade or age

Abstract: The major risk of rebleeding after SAH is present within the first 6 to 12 hours. This risk of ultra-early rebleeding is highest for patients with poor grades. Securing ruptured aneurysms by surgery or coil placement on an emergency basis for all patients with SAH has a strong rational argument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(82 citation statements)
references
References 88 publications
(103 reference statements)
3
76
3
Order By: Relevance
“…Surgical skill level as assessed based on mortality rate The mortality rate for patients with ruptured cerebral aneurysms was 9.6% in the present study, lower than the 14-31% reported in Western countries 7,9,[11][12][13] and lower than the 8.8-48.5% in US studies that investigated relationships between case volume and outcome. 1,18) The mortality rate for patients with unruptured cerebral aneurysm was 0.2% in the present study, also lower than the 1.0-2.6% reported in Western countries.…”
Section: Discussioncontrasting
confidence: 52%
“…Surgical skill level as assessed based on mortality rate The mortality rate for patients with ruptured cerebral aneurysms was 9.6% in the present study, lower than the 14-31% reported in Western countries 7,9,[11][12][13] and lower than the 8.8-48.5% in US studies that investigated relationships between case volume and outcome. 1,18) The mortality rate for patients with unruptured cerebral aneurysm was 0.2% in the present study, also lower than the 1.0-2.6% reported in Western countries.…”
Section: Discussioncontrasting
confidence: 52%
“…Moreover, Laidlaw and Siu [15] emphasized the importance of ultra-early surgery because the major risk of rebleeding after SAH is present within the first 6 to 12 hours and the risk of ultra-early rebleeding is highest for poor-grade patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have described different treatment strategies for patients with poor-grade aneurysm, with early treatment being increasingly recommended [9,16,19,22,23,25,26,31]. Moreover, bultra-earlyQ surgery is often recommended because a major risk of rebleeding after SAH is present within the first 6 to 12 hours, and the risk of ultra-early rebleeding is highest for poor-grade patients [15]. While early surgery decreases the risk of rehemorrhage, it is often questioned because of concerns related to increased risk of surgical complications and the infliction of further damage to the already edematous brain caused by retraction and manipulation of cerebral vessels [5,6,10,11,14,27,29].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional approach to treat this condition suggests that surgery should be performed when the patients have recovered from the SAH or when their Hunt and Hess grade has reduced to level ≤III, since early surgery following SAH is considered to present a high risk, as is associated with brain swelling, bleeding and unstable vital signs (4). However, recent studies have observed that early rebleeding occurs mostly within 24 h of SAH, particularly in the first 6-12 h, when the risk of ultra-early rebleeding is highest (9)(10)(11)(12). Intracerebral hematoma, rebleeding and severe cerebral vasospasm may lead to serious neurologic deficit in the early time subsequent to SAH (8,9).…”
Section: Introductionmentioning
confidence: 99%